2015
DOI: 10.1021/acs.nanolett.5b04187
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Solvent-Assisted Sodium Ion Intercalation into Highly Crystalline Few-Layered Graphene

Abstract: A maximum sodium capacity of ∼35 mAh/g has hampered the use of crystalline carbon nanostructures for sodium ion battery anodes. We demonstrate that a diglyme solvent shell encapsulating a sodium ion acts as a "nonstick" coating to facilitate rapid ion insertion into crystalline few-layer graphene and bypass slow desolvation kinetics. This yields storage capacities above 150 mAh/g, cycling performance with negligible capacity fade over 8000 cycles, and ∼100 mAh/g capacities maintained at currents of 30 A/g (∼12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(173 citation statements)
references
References 43 publications
7
165
1
Order By: Relevance
“…In an effort to utilize graphite anodes, some groups have proposed the co-intercalation of Na and the solvent in graphite, forming ternary Na-solvent-graphite compounds. [333][334][335]468,469 ] Nevertheless, the following challenges remain. (i) The low specifi c capacity and high intercalation voltage will lead to low gravimetric/volumetric energies in full cell systems.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…In an effort to utilize graphite anodes, some groups have proposed the co-intercalation of Na and the solvent in graphite, forming ternary Na-solvent-graphite compounds. [333][334][335]468,469 ] Nevertheless, the following challenges remain. (i) The low specifi c capacity and high intercalation voltage will lead to low gravimetric/volumetric energies in full cell systems.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Its enhanced broadening involves a structural modification of the interlayer spacing to allow sodium diffusion. Recently, Cohn et al 51 showed stable capacity of ca. 150 mA h g −1 , suggesting a stoichiometry of Na(Diglyme) x C 15 , that is in agreement with previous reports on chemically derived stage 1 Na + ternary graphite intercalation compounds (GICs).…”
Section: Gsm-b Gsm-br G Dmentioning
confidence: 99%
“…11,[38][39][40] However, these materials still have limitations such as low capacity, poor rate capability, rapid capacity fade and complex preparation process.…”
Section: -37mentioning
confidence: 99%